Intelligent mineralization material for drinking water based on electrical stimulation response and preparation method and application thereof

CN122586236BActive Publication Date: 2026-10-23CHINA WATER INVESTMENT CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610997333.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-23
Estimated Expiration
2046-07-06

AI Technical Summary

Technical Problem

[0011]有鉴于此,本发明提供一种基于电刺激响应的饮用水智能矿化材料及制备方法与应用,以解决现有技术中矿化强度无法动态调节、响应滞后且不可逆、长期使用易钝化结垢等技术问题

Benefits of technology

第一,本发明通过组分的优化设计,结合弱电场参数调节,可主动控制矿化离子释放速率,突破传统材料“制备即固定”的被动释放模式,实现矿化强度的精准可调与个性化饮水需求适配;利用电场对水凝胶网络及颗粒表面双电层的直接作用,将矿化强度调节的响应时间压缩至秒级别,且具备良好的可逆性,显著优于传统材料数小时至数天的响应速度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122586236B_ABST
    Figure CN122586236B_ABST
Patent Text Reader

Abstract

The application provides a kind of intelligent mineralization material of drinking water based on electric stimulation response and preparation method and application, belong to drinking water purification and mineralization technical field, the mineralization material, the mineralization material is with conductive polymer hydrogel as carrier, and inlay electric stimulation response mineralization core particle in the carrier, the application further provides a kind of preparation method of the mineralization material, including the following steps: preparation mineralization core particle;Preparation conductive polymer hydrogel;The mineralization core particle is mixed with the conductive polymer hydrogel, crosslinking agent is added to carry out crosslinking reaction, and the composite hydrogel of three-dimensional interpenetrating network structure is formed;Forming drying, obtain the intelligent mineralization material of drinking water.The mineral material of the application induces double electric layer reconstruction under electric field by means of conductive polymer hydrogel, actively controls the ion release rate of mineralization core particle and inhibits surface scale layer deposition, realizes long-acting stable intelligent mineralization and safe application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of drinking water purification and mineralization technology, specifically relating to intelligent mineralization materials for drinking water based on electrical stimulation response, their preparation methods, and applications. Background Technology

[0002] Mineralization of drinking water is an important technical means to improve drinking water quality and supplement the trace elements needed by the human body. With the increasing awareness of health, mineralization modules are widely integrated into household water purification equipment and portable drinking water devices, aiming to supplement purified drinking water with beneficial mineral ions such as calcium, magnesium, and potassium to meet the body's daily mineral needs.

[0003] Currently, the main technical solutions for drinking water mineralization materials are as follows: (1) Natural mineral materials Represented by natural minerals such as maifanite, zeolite, celestite, and tourmaline, mineralization is achieved by crushing, shaping, or directly filling the minerals into water channels, utilizing the natural dissolution properties of mineral ions in water. This type of material is relatively inexpensive and widely available.

[0004] (2) Ceramic-based mineralized materials Mineralized active components are mixed with ceramic raw materials and sintered at high temperature to form a porous ceramic body. This type of material slows down the ion release rate by controlling the porosity and pore size distribution of the ceramic, thereby improving the release stability to a certain extent.

[0005] (3) Encapsulated composite mineralization materials Mineralized active substances are encapsulated or coated with polymer materials (such as polyvinyl alcohol, sodium alginate, chitosan, etc.) to form a core-shell structure or a layered structure, and the barrier effect of the coating layer is used to delay ion release.

[0006] Currently, the following common technical challenges exist in the field of drinking water mineralization materials: (1) Poor stability of mineral ion release rate. The release behavior of mineral materials is affected by a variety of factors such as influent flow rate, water hardness, pH value, and temperature. It lacks self-adaptive adjustment ability, resulting in a large fluctuation range of effluent mineralization, which makes it difficult to meet the stability requirements of mineral ion concentration in drinking water standards.

[0007] (2) The mineralization intensity cannot be adjusted on demand. Existing materials are all passive release types. Once the preparation is completed, their mineralization performance is fixed. It is impossible to adjust the mineralization ion concentration in real time according to different groups of people (such as infants who need low mineralization and athletes who need to quickly replenish electrolytes) or different usage scenarios (daily drinking and post-exercise hydration). Personalized drinking water needs cannot be met.

[0008] (3) Long-term use easily leads to passivation and scaling. During long-term operation, mineralized materials are prone to the deposition of scale layers such as calcium carbonate and silicates on their surface and inside the pores. These scale layers not only block ion diffusion channels but also cover active dissolution sites, causing the material to gradually lose its mineralization ability. Users usually cannot intuitively determine whether the material has failed, which poses a water quality safety hazard.

[0009] (4) Complex structure and frequent replacement of consumables. Existing improvement solutions mostly rely on complex structural designs such as multi-layer composite and encapsulated core and shell, which not only increases the manufacturing difficulty and cost, but also limits the effective service life of the equipment to the weakest encapsulation layer or functional layer. Users need to replace the filter element frequently, resulting in a poor user experience.

[0010] In summary, existing drinking water mineralization materials generally rely on passive ion diffusion or release mechanisms from coating degradation. However, they still have key problems that urgently need to be solved, such as the inability to dynamically adjust mineralization intensity, delayed and irreversible response, easy passivation and scaling after long-term use, and complex structure and high maintenance costs. Summary of the Invention

[0011] In view of this, the present invention provides a smart mineralization material for drinking water based on electrical stimulation response, as well as its preparation method and application, to solve the technical problems in the prior art such as the inability to dynamically adjust the mineralization intensity, the lag and irreversibility of the response, and the tendency to passivate and scale after long-term use.

[0012] To achieve the aforementioned objectives, this invention provides an intelligent mineralization material for drinking water based on electrical stimulation response. The mineralization material uses a conductive polymer hydrogel as a carrier, and embeds electrically responsive mineralization core particles within the carrier. Specifically, the conductive polymer hydrogel network can generate a localized polarization effect under weak electrical stimulation, dynamically controlling the swelling degree and pore structure of the gel network, and inducing double-layer reconstruction on the surface of the mineralization core particles, thereby accelerating the directional migration and release of mineralized ions.

[0013] A method for preparing an intelligent mineralizing material for drinking water based on electrical stimulation response, as described in this invention, includes the following steps: S1. Preparation of mineralized core particles: Celestite and zeolite are mixed, and electrically activated minerals are added. After crushing, sieving, granulation, drying and calcination, porous composite ceramic mineralized core particles are obtained. S2. Preparation of conductive polymer hydrogel: Dissolve pyrrole monomer in acidic aqueous solution, add oxidant, and polymerize under low temperature conditions to obtain conductive polymer hydrogel; S3. Composite modification: The mineralized core particles are mixed with the conductive polymer hydrogel, and a crosslinking agent is added to carry out a crosslinking reaction to form a composite hydrogel with a three-dimensional interpenetrating network structure. S4. Molding and Drying: The composite hydrogel is injected into a mold and then pre-frozen and freeze-dried to obtain the intelligent mineralization material for drinking water.

[0014] Preferably, the mass ratio of celestite to zeolite in S1 is 1~2:1.

[0015] Preferably, the electroactivated mineral in S1 is CaCl2 and / or MgSO4, and the doping amount of the electroactivated mineral is 0.5 to 1.5 wt% of the total mass of celestite and zeolite.

[0016] More preferably, the electroactivated mineral in S1 is a mixture of CaCl2 and MgSO4, wherein the doping amount of CaCl2 is 1.0 wt% of the total mass of celestite and zeolite, and the doping amount of MgSO4 is 0.5 wt% of the total mass of celestite and zeolite.

[0017] Preferably, the binder used in the granulation process described in S1 is sodium silicate, and the pore-forming agent is sodium bicarbonate.

[0018] Preferably, the acidic aqueous solution in S2 is 0.1 M hydrochloric acid, the oxidant is ammonium persulfate, the molar ratio of the oxidant to the pyrrole monomer is 1:1, the polymerization reaction temperature is 4°C, and the concentration of the pyrrole monomer is 0.1 M.

[0019] Preferably, the mass ratio of the mineralized core particles to the conductive polymer hydrogel in S3 is 1:3-4.

[0020] Preferably, the crosslinking agent in S3 is glutaraldehyde or an EDC / NHS crosslinking system.

[0021] A drinking water mineralization device based on electro-response control, comprising: A responsive mineralization core, wherein the responsive mineralization core is composed of the intelligent mineralization material for drinking water described in this invention; The electrode system includes a working electrode that holds the mineralized core, and a reference electrode and auxiliary electrodes disposed on the periphery, for providing stable electric field conditions; The intelligent control unit includes a voltage / current regulation circuit, a real-time detection module, a control logic unit, and a human-machine interface, which is used to adjust the electric field parameters according to the detection signal to achieve the adjustment of the mineralization release rate. A flow reaction chamber is provided in the path of drinking water to contain the mineralized core and ensure that the water is in contact with it; An insulating encapsulation structure is used to protect the electrical safety of the electrodes and the electronic control system.

[0022] Specifically, the working electrode is a conductive sheet made of titanium mesh or carbon cloth; the real-time detection module includes a pH sensor, a conductivity sensor, and a temperature sensor; the intelligent control unit is configured to adjust the voltage or current applied to the electrode system in real time according to the influent water quality, water flow rate, or user input commands, so as to switch between low mineralization mode and high mineralization mode.

[0023] The intelligent mineralization material for drinking water based on electrical stimulation response provided by the present invention uses conductive polymer hydrogel as a three-dimensional porous carrier and embeds electrical stimulation responsive mineralization core particles in the carrier.

[0024] This invention achieves high-performance control that traditional materials cannot achieve by optimizing three key process parameters: the amount of electroactivated minerals in the mineralized core particles, the mass ratio of the mineralized core particles to the conductive polymer hydrogel, and the amount of crosslinking agent added to the hydrogel. These parameters directly determine the material's electroresponse rate, controllability, and long-term stability, and are the core innovations of this invention.

[0025] Under the stimulation of a weak electric field, and based on optimized parameters, the conductive polymer hydrogel network generates a local polarization effect. This effect synergistically achieves precise control over the release behavior of mineralized ions from two levels: (a) Dynamic regulation of diffusion channels This invention optimizes the mass ratio of mineralized core particles to conductive polymer hydrogel to 1:3-4, while controlling the amount of crosslinking agent added to 0.25 wt%. This ratio ensures the formation of a continuous and complete three-dimensional conductive network, allowing the local polarization effect to be fully transmitted throughout the material. The amount of crosslinking agent ensures sufficient flexibility in the gel network, providing a structural basis for swelling and shrinkage. Based on this, the local polarization effect can alter the charge distribution and interchain interactions of the gel network, thereby dynamically controlling the swelling degree and pore structure of the hydrogel. When the gel network shrinks, the pore size decreases, the ion diffusion channels narrow, and the release rate of mineralized ions decreases; when the gel network swells, the pore size increases, the ion diffusion channels widen, and the release rate of mineralized ions increases. Through precise control of the electric field parameters, reversible and continuous adjustment of the mineralized ion diffusion flux can be achieved.

[0026] If the ratio deviates from this parameter range: too low a ratio will result in insufficient conductive hydrogel content, making it impossible to form a continuous conductive network, and the polarization effect will only be effective on the surface of the material; too high a crosslinking agent content will result in excessive network rigidity, making it impossible to achieve dynamic changes in swelling and shrinkage, ultimately leading to a significant decrease in response rate and loss of dynamic control capability.

[0027] (ii) Reduction of the ion desorption energy barrier This invention optimizes the doping amount of electrically activated minerals to 0.5~1.5 wt%, ensuring the formation of a stable responsive electric double layer on the surface of the mineralized core particles, providing a structural basis for the electric field-triggered reconstruction effect. The electric field can induce efficient reconstruction of this electric double layer, significantly altering the charge density and ion distribution on the particle surface, thereby greatly reducing the activation energy barrier required for the desorption of mineralized ions from the particle surface and accelerating the directional migration and release of mineralized ions into the aqueous phase.

[0028] If the doping amount deviates from this parameter range: when the doping amount is less than 0.5 wt%, the response capability of the double layer is insufficient, the ion desorption energy barrier cannot be effectively reduced, and both the electrical response rate and amplitude will be significantly reduced; when the doping amount is greater than 1.5 wt%, the concentration of statically released minerals will exceed the standard, which does not meet the drinking water safety standard. Therefore, this range is the optimal range that balances response performance and safety standards.

[0029] Based on the optimized design of the above parameters, the material of this invention can achieve modulation characteristics far exceeding those of traditional materials under weak electrical stimulation: Second-level rapid response: Electric field stimulation can be directly applied to the gel network and particle surface without relying on material degradation or passive diffusion processes. The adjustment of ion release rate can be completed within 1 to 2 seconds, and the response speed is far superior to that of traditional materials. Reversible control: After the electric field is removed, thanks to the reasonable network structure, the swelling degree and pore structure of the gel network can be completely restored to the initial state, and the ion release rate is restored accordingly. It has excellent reversibility and can achieve tens of thousands of stable cycle adjustments. Anti-scaling and anti-passivation: Electric field-induced double-layer reconstruction can inhibit the nucleation and deposition of scale such as calcium carbonate on the particle surface. At the same time, the dynamically adjusted pore structure can reduce the accumulation of impurities inside the material, effectively avoiding scaling and passivation problems during long-term use.

[0030] Compared with the prior art, the present invention has the following beneficial effects: First, by optimizing the design of the components and adjusting the weak electric field parameters, this invention can actively control the release rate of mineralized ions, breaking through the passive release mode of traditional materials that are "fixed upon preparation". This enables precise adjustment of mineralization intensity and adaptation to personalized drinking water needs. By utilizing the direct effect of the electric field on the hydrogel network and the double electric layer on the particle surface, the response time for adjusting mineralization intensity is compressed to the second level, and it has good reversibility, which is significantly better than the response speed of traditional materials that takes several hours to several days.

[0031] Secondly, by ensuring the electric field-induced double-layer reconstruction effect, this invention can effectively suppress the nucleation and deposition of scale such as calcium carbonate on the material surface, avoiding the coverage of active sites and the blockage of ion release channels. Under the same operating cycle, the mineralization efficiency decay rate is significantly lower than that of traditional materials, effectively solving the problem of insufficient stability during long-term service. At the same time, the mineralization core particles are directly embedded in the optimized conductive polymer hydrogel as a carrier, without relying on multi-layer coating or complex layered structures. The preparation process is simple and the cost is controllable. The material has reversible controllability and anti-passivation properties, eliminating the need for frequent filter replacement and significantly reducing preparation and maintenance costs.

[0032] Third, all materials used in this invention meet the safety standards for food contact materials, have good biocompatibility, and have no risk of harmful substances being released when working under weak electric field conditions. This ensures that the mineral content of the effluent is stably controlled within a suitable range, meeting relevant drinking water safety standards. Attached Figure Description

[0033] Figure 1 The intelligent mineralizing material for drinking water in a specific embodiment of the present invention / Ca before and after applying an electric field to the mineralizing material 2+ Release concentration comparison chart; Figure 2 The graph shows the test results of the response speed and reversibility of the smart mineralization material / mineralization material for drinking water in a specific embodiment of the present invention. Figure 3 This is a graph showing the flow rate adaptability test results of the intelligent mineralizing material / mineralizing material for drinking water in a specific embodiment of the present invention. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0035] Example 1 This embodiment provides a method for preparing a smart mineralization material for drinking water based on electrical stimulation response, including the following steps: S1. Preparation of mineralized core particles: Celestite and zeolite are mixed in a mass ratio of 1:1. The mixture is repeatedly washed until the effluent is clear and free of turbidity. Then, it is placed in an oven and dried at 60°C in a vacuum environment for 6 hours. After drying, it is placed in an ore crusher and crushed. After multiple crushings, it is passed through a 250-mesh standard sieve to obtain the crushed ore raw material. Then, based on the total mass of celestite and zeolite, 3 wt% of binder (sodium silicate, Aladdin, item number S302439, Na2O≥18%, SiO2≥60%) and 3 wt% of pore-forming agent (sodium bicarbonate, Aladdin, item number S683672, purity≥99.8%) are added to obtain a composite ceramsite mineralized material with certain mechanical strength and porosity after subsequent calcination, and 0.5 wt% of CaCl2 (Aladdin, item number C431202, purity≥97%) is added to the mixture. Turn on the rotary granulator and adjust its speed to between 30 and 40 r / min. Add the powdered raw materials in batches, spraying deionized water during the process to accelerate particle formation. The total amount of water added is equal to the total amount of powdered raw materials. 12 wt% of the mass. During the granulation process, round particles with suitable particle size are screened out using a 6 mm standard sieve. Particles that do not meet the particle size requirements are returned to the round pot for regranulation, and finally particles with a particle size distribution in the range of 6~12 mm are obtained. S2. Preparation of conductive polymer hydrogel: Pyrrole (Aladdin, catalog number P108479) is used. Monomers with a purity ≥ 99% were dissolved in a 0.1 M hydrochloric acid (HCl, Aladdin, catalog number H399657, 99% purity) aqueous solution, with the concentration of pyrrole monomer set at 0.1 M. Ammonium persulfate (APS) was then added as an oxidant at a monomer-to-oxidant molar ratio of 1:1. The reaction system was maintained at 4°C (low temperature controls polymerization rate and structural uniformity) and reacted magnetically for 8 hours. After the reaction was complete, a black conductive gel structure gradually formed. This conductive gel was soft and structurally inhomogeneous. To improve the uniformity of its subsequent composite with inorganic particles, it needed to be cut into small pieces (approximately 1 cm). 3 To break down the internal nucleation and agglomeration structure, ultrasonic dispersion treatment (40 kHz, 15 minutes) is then applied to make the gel form a finer dispersed phase, enhancing its interfacial contact with nanoparticles and composite efficiency, thereby improving the consistency and mineralization properties of the composite material and obtaining a conductive polymer hydrogel. S3. Composite Modification: The mineralized core particles are mixed with the conductive polymer hydrogel, and a crosslinking agent is added to carry out a crosslinking reaction. Glutaraldehyde (Aladdin, product number G359127, 25% aqueous solution, purity 99%) can be used. The amount added is 0.25 wt% of the total mass of the mixture. The crosslinking reaction is carried out at room temperature for 24 hours to form a composite hydrogel network with a three-dimensional interpenetrating structure. This structure can realize the controlled release of minerals and also has a certain conductivity, which is beneficial to the subsequent ozone electrocatalytic reaction. The mass ratio of the mineralized core particles to the conductive polymer hydrogel is 1:4. S4. Molding and Drying: The composite hydrogel is injected into a mold (designed to mimic the columnar structure of a water dispenser filter cartridge, with dimensions such as Φ50×100 mm), pre-frozen at -20℃ for 4 hours, and then subjected to sublimation drying in a freeze dryer (-50℃, 24 hours) to obtain the intelligent mineralization material for drinking water. This process removes free water from the system, fixes the molding structure, and ultimately obtains a composite mineralization material block with a stable structure, uniform pores, and controllable ion release capability. The resulting product has moderate mechanical strength and can be inserted into a drinking water purification device for use in conjunction with an ozone aeration system to achieve continuous mineralization and electro-responsive functions.

[0036] Example 2 This embodiment provides a method for preparing a smart mineralization material for drinking water based on electrical stimulation response, including the following steps: S1. Preparation of mineralized core particles: Celestite and zeolite are mixed in a mass ratio of 2:1. After washing, drying, and pulverizing, a binder (sodium silicate, Aladdin, item number S302439, Na2O≥18%, SiO2≥60%) and a pore-forming agent (sodium bicarbonate, Aladdin, item number S683672, purity≥99.8%) with a mass fraction of 6 wt% based on the total mass of celestite and zeolite, and an electro-activated mineral are added to obtain powdered raw materials for granulation. The electro-activated mineral is a mixture of CaCl2 (Aladdin, item number C431202, purity≥97%) and MgSO4 (Aladdin, item number M485462, purity≥99.5%), with a CaCl2 doping amount of 1 wt% and a MgSO4 doping amount of 0.5 wt% based on the total mass of celestite and zeolite. wt%, enabling the material to control the ion release rate under the action of an electric field; S2. Preparation of conductive polymer hydrogel: Pyrrole (Aladdin, catalog number P108479) is used. The monomer (purity ≥99%) was dissolved in a 0.1 M hydrochloric acid (HCl, Aladdin, catalog number H399657, purity 99%) aqueous solution, with the concentration of pyrrole monomer set at 0.1 M. Ammonium persulfate (APS, Aladdin, catalog number A112448, purity ≥98%) was then added as an oxidant at a monomer to oxidant molar ratio of 1:1. The reaction system was maintained at 4°C (low temperature controls polymerization rate and structural uniformity) and reacted magnetically for 8 hours. After the reaction was complete, the system gradually formed a black conductive gel structure, yielding a conductive polymer hydrogel. S3. Composite Modification: The mineralized core particles are mixed with the conductive polymer hydrogel, and an EDC / NHS crosslinking system (EDC, i.e., 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, Aladdin, catalog number E106172, purity ≥98%; NHS, i.e., N-hydroxysuccinimide, Aladdin, catalog number H109330, purity ≥98%, EDC and NHS in a 2:1 molar ratio) is added as a crosslinking agent to carry out a crosslinking reaction. The crosslinking reaction is carried out at room temperature for 24 hours to form a composite hydrogel with a three-dimensional interpenetrating structure. The mass ratio of the mineralized core particles to the conductive polymer hydrogel is 1:3.5. S4. Molding and Drying: The composite hydrogel is injected into a mold and pre-frozen at -20°C for 4 hours, then placed in a freeze dryer for sublimation drying (-50°C, 24 hours) to obtain the intelligent mineralized drinking water material.

[0037] Example 3 This embodiment provides a method for preparing a smart mineralization material for drinking water based on electrical stimulation response, including the following steps: S1. Preparation of mineralized core particles: Celestite and zeolite are mixed in a mass ratio of 1.5:1. After washing, drying, and pulverizing, the mixture is added based on the total mass of celestite and zeolite. Granulation was performed using a powdered raw material consisting of 6 wt% binder (sodium silicate, Aladdin, item number S302439, Na2O≥18%, SiO2≥60%), 3 wt% pore-forming agent (sodium bicarbonate, Aladdin, item number S683672, purity≥99.8%), and electroactivated minerals. The electroactivated minerals were a mixture of CaCl2 (Aladdin, item number C431202, purity≥97%) and MgSO4 (Aladdin, item number M485462, purity≥99.5%), with CaCl2 doping at 1 wt% and MgSO4 doping at 0.3 wt% based on the total mass of celestite and zeolite. S2. Preparation of conductive polymer hydrogel: Pyrrole (Aladdin, catalog number P108479) is used. The monomer (purity ≥99%) was dissolved in a 0.1 M hydrochloric acid (HCl, Aladdin, catalog number H399657, purity 99%) aqueous solution, with the concentration of pyrrole monomer set at 0.1 M. Ammonium persulfate (APS, Aladdin, catalog number A112448, purity ≥98%) was then added as an oxidant at a monomer to oxidant molar ratio of 1:1. The reaction system was maintained at 4°C (low temperature controls polymerization rate and structural uniformity) and reacted magnetically for 8 hours. After the reaction was complete, the system gradually formed a black conductive gel structure, yielding a conductive polymer hydrogel. S3. Composite modification: The mineralized core particles are mixed with the conductive polymer hydrogel, and glutaraldehyde (Aladdin, product number G359127, 25% aqueous solution, purity 99%) crosslinking agent is added to carry out crosslinking reaction. The crosslinking reaction is carried out at room temperature for 24 hours to form a composite hydrogel with a three-dimensional interpenetrating structure. The mass ratio of the mineralized core particles to the conductive polymer hydrogel is 1:3. S4. Molding and Drying: The composite hydrogel is injected into a mold and pre-frozen at -20°C for 4 hours, then placed in a freeze dryer for sublimation drying (-50°C, 24 hours) to obtain the intelligent mineralized drinking water material.

[0038] Comparative Example 1 Traditional natural calcite ore mineralization material (Aladdin, item number C755881, particle size 6~12 mm, calcium carbonate purity ≥99%) was used directly as the mineralization material without conductive gel composite treatment.

[0039] Comparative Example 2 This comparative example provides a method for preparing a mineralized material. The difference between this method and Example 2 is that the total mass of celestite and zeolite is used as the basis in this comparative example, the doping amount of CaCl2 is 0.2 wt%, the doping amount of MgSO4 is 0.1 wt%, and the doping amount of electroactivated minerals is 0.5~1.5 wt% lower than that of this invention. The remaining steps and parameters are the same as in Example 2, and the mineralized material is finally obtained.

[0040] Comparative Example 3 This comparative example provides a method for preparing a mineralized material. The difference between this method and Example 2 is that the mass ratio of the mineralized core particles to the conductive polymer hydrogel in this comparative example is 1:1, which is lower than the optimized range of 1:3 to 4 of this invention. The remaining steps and parameters are the same as in Example 2, and the mineralized material is finally obtained.

[0041] The drinking water smart mineralization materials / mineralization materials from Examples 1-3 and Comparative Examples 1-3 were subjected to standardized electro-response release tests. The test conditions were: the influent was deionized water, and the test ambient temperature was 25°C. The ion release performance under different conditions was tested, specifically including the following steps: (1) Set up an electrical stimulation release test platform: Use a small DC power supply (0.5~3V), electrodes (titanium electrodes or carbon rods) to clamp the two ends of the drinking water smart mineralization material / mineralization material, pass through flowing deionized water at a flow rate of 1 L / min, set different voltages and cycles, and collect the aqueous solution; (2) Water ion concentration: Ca was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). 2+ Mg 2 + Na +Equal release concentration; (3) Test release curve: Compare the ion release rate curves at different flow rates to observe the material’s dynamic adjustment capability and control precision.

[0042] Test results are as follows Figure 1 Under the condition of no electric field (0V), the static Ca of each material 2+ The release concentrations were as follows: 12.3 mg / L for Example 1, 18.5 mg / L for Example 2, 15.7 mg / L for Example 3, 11.8 mg / L for Comparative Example 1, and 18.1 mg / L and 25.3 mg / L for Comparative Example 2 and Comparative Example 3, respectively.

[0043] When a 2V DC electric field is applied, the sample Ca of the embodiment of the present invention 2+ The release concentration was significantly increased, especially for Ca in Example 1. 2+ The release concentration could be increased to 45.6 mg / L in Example 2, 62.3 mg / L in Example 3, and 52.1 mg / L in Example 3; while in the three comparative examples, after applying the same electric field, Ca... 2+ The release concentration increased by only 8-11%, far lower than the 230%-270% increase in the previous embodiment, indicating that the smart mineralization material for drinking water in the present invention has a significant electro-responsive release effect.

[0044] The drinking water smart mineralization materials / mineralization materials from Examples 1-3 and Comparative Examples 1-3 were used for response speed and reversibility tests. The test results are as follows: Figure 2 After the electric field is turned on, the ion concentration in the effluent of the samples in Examples 1-3 can achieve a rapid response within seconds: Example 1 reaches 90% of the stable release value within 1.2 seconds and reaches complete stability within 2.5 seconds; the response time of Example 2 is 1.5 seconds, and that of Example 3 is 1.3 seconds; while the samples in Comparative Examples 1-3 show no significant response change, with an increase of only 2-4%. After the electric field is turned off, the release concentration of the mineralized material sample prepared by the method of this invention can recover to the baseline release level within 3 seconds, exhibiting good response reversibility and enabling real-time switching of mineralization intensity.

[0045] The drinking water smart mineralization materials / mineralization materials from Examples 1-3 and Comparative Examples 1-3 were used to conduct flow rate adaptability and control accuracy tests. The test results are as follows: Figure 3 When the water flow rate increases from 0.5 L / min to 2 L / min, the Ca in Comparative Example 1... 2+The release concentration increased from 7.1 mg / L to 15.2 mg / L. The overall concentration fluctuation in Comparative Examples 2 and 3 exceeded 50%, making them unsuitable for drinking water scenarios with varying flow rates. However, the mineralizing material in Example 1 of this invention, by adjusting the flow rate of deionized water (dynamically adjusted from 0.5 L / min to 2 L / min), can reduce the calcium content in the effluent. 2+ The concentration was stably maintained at 30±0.8 mg / L, with a concentration control accuracy of up to 97.3%. In the mineralized materials prepared by the method of this invention, Examples 2 and 3 also maintained relatively stable Ca concentrations under the same flow rate variation conditions. 2+ The release trend shows that the mineralized material in Example 2 was maintained at approximately 60 mg / L, and the mineralized material in Example 3 was maintained at approximately 50 mg / L. The phenomenon of large fluctuations with increasing flow rate as observed in the comparative examples was not observed. This further demonstrates that the mineralized material prepared by the method of the present invention not only has significant electro-responsive release capability, but also maintains good mineralization concentration stability and control precision under different flow rate conditions. This further supports the comprehensive technical effects of dynamic regulation, rapid response and stable mineralization of the material of the present invention.

[0046] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. The scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing intelligent mineralization materials for drinking water based on electrical stimulation response, characterized in that, Includes the following steps: S1. Preparation of mineralized core particles: Celestite and zeolite are mixed in a mass ratio of 1 to 2:

1. Electro-activated minerals are added, and the mixture is then crushed, sieved, granulated, dried, and calcined to obtain porous composite ceramsite-like mineralized core particles. The electro-activated minerals are CaCl2 and / or MgSO4, and the doping amount of the electro-activated minerals is 0.5 to 1.5 wt% of the total mass of celestite and zeolite. S2. Preparation of conductive polymer hydrogel: Pyrrole monomer is dissolved in an acidic aqueous solution, an oxidant is added, and polymerization reaction is carried out under low temperature conditions to obtain conductive polymer hydrogel. The acidic aqueous solution is 0.1 M hydrochloric acid, the oxidant is ammonium persulfate, the molar ratio of the oxidant to the pyrrole monomer is 1:1, the polymerization reaction temperature is 4℃, and the concentration of the pyrrole monomer is 0.1 M. S3. Composite modification: The mineralized core particles are mixed with the conductive polymer hydrogel, and a crosslinking agent is added to carry out a crosslinking reaction to form a composite hydrogel with a three-dimensional interpenetrating network structure. The mass ratio of the mineralized core particles to the conductive polymer hydrogel is 1:3-4. S4. Molding and Drying: The composite hydrogel is injected into a mold and then pre-frozen and freeze-dried to obtain the intelligent mineralization material for drinking water.

2. The preparation method according to claim 1, characterized in that, The electroactivated minerals mentioned in S1 are a mixture of CaCl2 and MgSO4, with CaCl2 doping amounting to 1.0 wt% of the total mass of celestite and zeolite, and MgSO4 doping amounting to 0.5 wt% of the total mass of celestite and zeolite.

3. The preparation method according to claim 1, characterized in that, The binder used in the granulation process described in S1 is sodium silicate, and the pore-forming agent is sodium bicarbonate.

4. The preparation method according to claim 1, characterized in that, The crosslinking agent mentioned in S3 is glutaraldehyde or an EDC / NHS crosslinking system.

5. A smart mineralizing material for drinking water prepared by the method according to any one of claims 1-4, characterized in that, The intelligent mineralization material for drinking water uses a conductive polymer hydrogel as a carrier, and embeds electrically responsive mineralization core particles within the carrier.

6. A drinking water mineralization device based on electro-response control, characterized in that, include: A responsive mineralization core, wherein the responsive mineralization core is composed of the smart mineralization material for drinking water as described in claim 5; The electrode system includes a working electrode that holds the mineralized core, and a reference electrode and auxiliary electrodes disposed on the periphery, for providing stable electric field conditions; The intelligent control unit includes a voltage / current regulation circuit, a real-time detection module, a control logic unit, and a human-machine interface, which is used to adjust the electric field parameters according to the detection signal to achieve the adjustment of the mineralization release rate. A flow reaction chamber is provided in the path of drinking water to contain the mineralized core and ensure that the water is in contact with it; Insulated encapsulation structure.

Citation Information

Patent Citations

  • Monodisperse cerium oxide nanoparticle and preparation method thereof

    CN102557105A

  • Water quality improving agent and manufacturing method therefor

    JP2003094072A